IJCM_250A: Awareness and utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojna in Chhattisgarh State - A cross Sectional study - Sahu Dinesh Kumar; Verma Nirmal; Sharma Mini; Jaiswal Prashant; Dengani Monika (Wolters Kluwer Medknow Publications, 2024)
Background: Ayushman Bharat Pradhan Mantri Jan Arogya Yojna (PM-JAY) is the worlds largest health insurance/ assurance scheme fully financed by the government. It provides a cover of Rs. 5 lakhs per family per year for secondary and tertiary care hospitalization across public and private empaneled hospitals in India. Over 12 crore poor and vulnerable entitled families are eligible for these benefits. As of now, the total number of ration cards allotted to the people of Chhattisgarh are 57,14,798. Objective: To assess awareness and utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojna in Chhattisgarh State. Methodology: This community based cross-sectional study was conducted among the eligible beneficiaries in Chhattisgarh state. Multis stage cluster sampling used to select eligible beneficiaries. One district each from all five divisions of Chhattisgarh will be selected then 5 clusters (3 urban and 2 rural area) will be selected from each district. Data was collected face to face interview by using semi structured questionnaire. Data was managed in MS- Excel and analysed using suitable statistical software (SPSS v21) and P Value Results: The study shows 300 (80.9%), and 68(18.3%) participants are BPL & APL card holders respectively and 3(.8%) do not have any card. Out of 371 participants, 92(24.8%) are not enrolled in the scheme. Among study participants, only 90% were aware of the AB-PMJAY, and only 197 (53%) utilized the scheme and get benefitted. Conclusion: This study concluded that despite AB-PMJAY potentially providing cashless financial protection to beneficiaries, some of the study population is still unaware of AB-PMJAY. A quarter of the participants were not enrolled in the scheme, indicating potential gaps in the implementation or accessibility of the program.